The impact of the earthquake in northwestern Turkey on the continuous ambulatory peritoneal dialysis patients who were living in the earthquake zone. - (:unkn) unknown (My University, 2000)
In August 1999, an earthquake of magnitude 7.8 on the Richter scale hit northwestern Turkey. The epicenter was in Izmit, an industrial town about 60 km from Istanbul. This paper presents data about the fate of CAPD patients who were living in that region at the time of the earthquake. A total of 42 continuous ambulatory peritoneal dialysis (CAPD) patients (14 females, 28 males; 37 adult patients, 5 pediatric patients) were permanent residents of the earthquake region. They were followed in the CAPD units of Marmara University Hospital (n = 6), Gata Military Hospital (n = 2), and Goztepe SSK Hospital (n = 10, including the 5 pediatric patients) in Istanbul, and in Uludag University Hospital in Bursa (n = 6) and Kocaeli University Hospital in Izmit (n = 18). Two CAPD patients, together with their families, died under the rubble in the city of Golcuk. One CAPD nurse from Kocaeli University Hospital in Izmit also died a victim of the earthquake. One patient who lived in Golcuk was under the rubble for 3 hours; she was rescued with no crush injuries and was able to continue with CAPD 24 hours after her rescue. Eight patients reported that their homes were completely destroyed during the earthquake, while nine patients reported serious damage to their houses. Ten patients had to move to other towns to live with relatives because their homes were no longer suitable for habitation, and twelve patients had to stay permanently in tents provided by the Red Cross. All of the patients were able to continue their CAPD therapy and had no interruption in the supply of their CAPD solutions. Four patients on continuous cycling peritoneal dialysis (CCPD) therapy continued to use their HomeChoice machines (Baxter Healthcare Corporation, Deerfield, IL, U.S.A.) even while living in a tent. CAPD patients from the Kocaeli University Hospital had to be temporarily referred to other CAPD centers in Istanbul and Bursa because the Kocaeli University Hospital was seriously damaged in the earthquake. We expect that these major changes in quality of life circumstances will have an important impact on the morbidity of these patients, especially in regard to the rate of peritonitis and the adequacy of dialysis.